Association between expectations and clinical outcomes in online v. face-to-face therapy - an individual participant data meta-analysis - Pontén, Moa; Jonsjö, Martin; Vadenmark, Viktor; Moberg, Erica; Grannas, David; Andersson, Gerhard; Boersma, Katja; Hedman-Lagerlöf, Erik; Kleinstaeuber, Maria; Weise, Cornelia; Kaldo, Viktor; Ljótsson, Brjánn; et al. (Psychological Medicine, 2023)
Background Online treatments are increasing in number and are currently available for a wide range of clinical problems. To date little is known about the role of treatment expectations and other placebo-like mechanisms in online settings compared to traditional face-to-face treatment. To address this knowledge gap, we analyzed individual participant data from randomized clinical trials that compared online and face-to-face psychological interventions. Methods MEDLINE (Ovid) and PsycINFO (Ovid) were last searched on 2 February 2021. Randomized clinical trials of therapist guided online v. face-to-face psychological interventions for psychiatric or somatic conditions using a randomized controlled design were included. Titles, abstracts, and full texts of studies were independently screened by multiple observers. The Preferred Reporting Items for Systematic Reviews and Meta-analyses guideline was followed. Authors of the matching trials were contacted for individual participant data. Ratings from the Credibility and Expectancy Questionnaire and the primary outcome measure from each trial were used to estimate the association between expectation ratings and treatment outcomes in online v. face-to-face interventions, using a mixed-effects model. Results Of 7045 screened studies, 62 full-text articles were retrieved whereof six studies fulfilled the criteria and provided individual participant data (n = 491). Overall, CEQ ratings predicted clinical outcomes (β = 0.27) at end of treatment with no moderating effect of treatment modality (online v. face-to-face). Conclusions Online treatment appears to be equally susceptible to expectancy effects as face-to-face therapy. This furthers our understanding of the importance of placebo-like factors in online treatment and may aid the improvement of healthcare in online settings.
CRIS-Team Scopus Importer:2024-03-27
Keywords: CEQ; face-to-face therapy; individual participant data meta-analysis; online therapy; randomized clinical trials; Treatment expectation